Trends in Global Dental Care Access: Barriers, Equity, and Innovations - Akeel, Samahir Siraj Othman; Khamis, Adnan Madni Mohamed; Alamri, Yousef Mohamed Ali; Alharbi, Nuha Hussain; Alalshi, Sawsan Abdulkader Sadek; Aqely, Mona Ali Mohammed; Battawi, Rowaida Ibrahim; Kelantan, Marwah Mohammed Abdulsamad; Alnjmi, Fatma Abdullah; Samkari, Esraa Kamal; et al. (Journal of Posthumanism, 2025)
Dental care is an essential component of overall health, yet access remains highly uneven across nations. While advances in diagnostic and therapeutic technologies have expanded possibilities for treatment, large segments of the global population still face significant barriers to receiving even basic care (Tartaglia, 2021; Dyar, 2022). In many low- and middle-income regions, shortages of trained personnel and the high cost of equipment limit service availability. Conversely, high-income countries benefit from sophisticated systems, but disparities persist among marginalized groups.